Rasa3 deficiency minimally affects thrombopoiesis but promotes severe thrombocytopenia due to integrin-dependent platelet clearance - Robert H. Lee; Dorsaf Ghalloussi; Gabriel L. Harousseau; Joseph P. Kenny; Patrick A. Kramer; Fabienne Proamer; Bernhard Nieswandt; Matthew J. Flick; Christian Gachet; Caterina Casari; Anita Eckly; Wolfgang Bergmeier (JCI Insight, 2022)
Platelet homeostasis is dependent on a tight regulation of both platelet production and clearance. The small GTPase Rap1 mediates platelet adhesion and hemostatic plug formation. However, Rap1 signaling is also critical for platelet homeostasis as both Rap1 deficiency and uninhibited Rap1 signaling lead to marked thrombocytopenia in mice. Here, we investigated the mechanism by which deficiency in Rasa3, a critical negative regulator of Rap1, causes macrothrombocytopenia in mice. Despite marked morphological and ultrastructural abnormalities, megakaryocytes in hypomorphic Rasa3hlb/hlb (R3hlb/hlb) or Rasa3–/– mice demonstrated robust proplatelet formation in vivo, suggesting that defective thrombopoiesis is not the main cause of thrombocytopenia. Rather, we observed that R3hlb/hlb platelets became trapped in the spleen marginal zone/red pulp interface, with evidence of platelet phagocytosis by macrophages. Clearance of mutant platelets was also observed in the liver, especially in splenectomized mice. Platelet count and platelet life span in Rasa3-mutant mice were restored by genetic or pharmacological approaches to inhibit the Rap1/talin1/αIIbβ3 integrin axis. A similar pattern of splenic clearance was observed in mice injected with anti-αIIbβ3 but not anti–glycoprotein Ibα platelet-depleting antibodies. In summary, we describe a potentially novel, integrin-based mechanism of platelet clearance that could be critical for our understanding of select inherited and acquired thrombocytopenias.